Interven????es em sala de aula voltadas para estudantes com Transtorno de D??ficit de Aten????o e Hiperatividade - TDAH: efeitos sobre os repert??rios caracter??sticos do transtorno - Santos, Waleska Mascarenhas dos (2017)
There is an agreement in the contemporary literature that multimodal interventions are best indicated for attention-deficit/hyperactivity disorder (ADHD). On this perspective, interventions implemented in the school context, especially in the classroom, are relevant for the educational process from students with this diagnosis. In this context, typical ADHD behaviors are especially dysfunctional and also contributes on school failure and dropout. The aim of the present study was to analyze the effects of two teaching strategies on typical problem ADHD behaviors: ClassWide Peer Tutoring and Highlighted Words. Using a multiple baseline across participants design, three elementary school students from a public school, diagnosed with ADHD, were exposed to both strategies. Results showed reduction in typical hyperactivity/impulsivity and attention deficit repertoires from baseline levels for all participants. These data replicate and extend the results of prior studies which also showed interventions effects however in academic tasking behaviors.